The entanglement of culture, leadership and performance in information systems development projects - Geeling, Sharon (Department of Information Systems, 2019)
Information systems (IS) development represents a significant area of research interest in the IS discipline. Despite this interest, IS development projects consistently fall short in delivering anticipated outcomes within time, quality and cost constraints. Attempts by researchers to uncover contributors to high failure rates are complicated by fragmented views of the nature of the problem. These range from challenges to the validity of performance reports to contesting the conceptualization of success. Furthermore, there is a tendency in practice to address immediate symptomatic problems of IS project failure rather than resolve the fundamental issues. Consequently, recent measures indicate that 48% of IS projects fail to meet time commitments, 33% exceed their budget, 32% don’t achieve their business objectives and 15% fail outright. This PhD thesis presents research to explore and offer explanatory theory of how culture and leadership are implicated in the performance of IS development projects. Importantly, IS development is positioned as a form of social interaction. Thus, an understanding of the social context and the situated meanings that arise through social interaction are necessary conditions to effectively explore this research topic. Within this context the study reveals the performative nature of IS development work and offers explanations for the actions of organizational leaders and IS technical specialists involved in IS development. An interpretive research paradigm and inductive reasoning were adopted for this research and understanding is developed through a hermeneutic mode of inquiry. Two IS projects responsible for delivering strategic benefit to an organization in the financial services sector are the two cases in this study. Qualitative data were collected through interviews, observation and documentary evidence between January 2017 and June 2017. The nature of the relationships between culture, leadership and performance in the course of IS development work was revealed through two analytical iterations. The first iteration used the theory of Cultural Implications in Information Systems Development as a structural framework to support a thematic analysis of the data. A second iteration used frame analysis as a theoretical foundation to examine the interplay of culture, leadership and performance through a within-case and cross-case analysis of the two cases. Key contributions from this research include the development of a conceptual model explaining cultural implications in IS development, the development of an explanatory theory of the entangled nature of culture and leadership and the performance of IS projects, and 11 propositions that offer a basis for testing the emergent theory in future empirical studies. The findings from the research also reveal the performative nature of IS development work and identify concepts important to organizational managers and IS technical specialists. While the theory emerged in the context of IS development projects and the concepts in the emergent theory are central to the practice of IS development, each could be equally relevant to other IS phenomena where culture, leadership and performance are implicated, such as IS management and offshoring. The grounding of theoretical concepts to empirical data enabled the application of the theory to practice; practical guidelines are offered in respect of the influences of culture and leadership on the performance of IS development projects. This research supports the suitability of the Cultural Dynamics Model as a sensitizing lens for data collection in interpretive studies where culture is implicated.